Women Activists and Civil Rights Leaders in Auto/Biographical Literature and Films (Springer International Publishing, 2018)
This collective book offers new insight on the genres of biography and autobiography by examining the singular path of those deemed to be 'outsiders', such as Winnie Mandela, Ida B. Wells, Malcolm X and Harvey Milk. Its specific focus on these female leaders and civil rights activists, who refused to be constrained by gender, race and class, shifts attention away from the great men of history and places it solely on those who have transformed their personal lives into a fight for collective goals. With an interdisciplinary approach that looks at literature, cinema and cultural studies, Women Activists and Civil Rights Leaders in Auto/Biographical Literature and Cinema argues that life writing is a key source of artistic creativity and activism which enables us to take a fresh look at history. .